HUBUNGAN KECEMASAN DAN PROKRASTINASI AKADEMIK TERHADAP HASIL BELAJAR MAHASISWA JURUSAN PENDIDIKAN TEKNIK INFORMATIKA UNIVERSITAS PENDIDIKAN GANESHA - Kristianti, Komang Devi; Wahyuni, Dessy Seri; Sunarya, I Made Gede (KARMAPATI (Kumpulan Artikel Mahasiswa Pendidikan Teknik Informatika), 2015)
This study aims to determine the relationship between anxiety with learning outcomes , the relationship between Academic Procrastination with learning outcomes , as well as the relationship between anxiety and Academic Procrastination together with the learning outcomes of students majoring in pendidikan teknik informatika Undiksha.This study is a correlation study is ex post - facto that consists of two independent variables , namely anxiety ( X1 ) and the Academic Procrastination ( X2 ) , and the dependent variable is the Learning Outcomes ( Y ) . The population in this study as many as 410 people and as many as 202 samples run respondents . Data X1 , X2 , and Y is obtained through a questionnaire . The collected data were analyzed using parametric statistical tests performed prerequisite is the test of normality , linearity , and multicollinearity .The results showed : ( 1 ) There is a positive and significant relationship between anxiety with learning outcomes of students majoring in informatics engineering education . Directions relationship kecemasandan Learning Outcomes are not unidirectional and have a very low level of relationship . ( 2 ) There is a positive and significant relationship between Academic Procrastination with student learning outcomes informatics engineering education . Direction of the relationship and Learning Outcomes Academic Procrastination is the opposite direction and has a very low level of relationship . ( 3 ) There is a positive and significant relationship between anxiety and Academic Procrastination with learning outcomes of students majoring in informatics engineering education . The results of multiple regression in hypothesis testing regression equation Y = X 4,112- 0,005 - 0,006 X2 . Direction of the relationship of anxiety and Academic Procrastination with Learning Results are positive and have a very low level of relationship .